Grim Tuesday - Nix, Garth (New York : Scholastic, 2004)
Seventh-grader Arthur Penhaligon returns to the parallel universe known as the House to fight his latest enemy, Grim Tuesday, whose greed threatens to destroy both the House and the Earth.
008-0012
Keywords: Greed -- Fiction; Space and time -- Fiction; Magic -- Fiction; Asthma -- Fiction; Responsibility -- Fiction; Fantasy